Ultimate guide to social media marketing - Butow, Eric; Allton, Mike; Herman, Jenn; Liu, Stephanie; Robinson, Amanda (Entrepreneur Press, 2020)
"Ultimate Guide to Social Media Marketing takes readers through a 360-degree perspective of social media marketing in businesses, from strategy to tactics, from organic to paid, from B2B to B2C, encompassing all of the current networks. Topics include: Why businesses need to embrace social media marketing Understanding today's social networks from big ones like Facebook and YouTube to emerging platforms Learning how to craft your business's social media strategy using today's formats How to leverage images and video in your social media outreach Leveraging chat bots, paid social media, and influencer marketing Building your business social marketing team Measure your social media outreach progress and improve your performance over time"--